Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/cdev.12700
|View full text |Cite
|
Sign up to set email alerts
|

“These Pretzels Are Making Me Thirsty”: Older Children and Adults Struggle With Induced‐State Episodic Foresight

Abstract: We explored children’s and adults’ ability to disengage from current physiological states when forecasting future desires. In Study 1, 8- to 13-year-olds and adults (N=104) ate pretzels (to induce thirst) and then predicted and explained what they would want tomorrow, pretzels or water. Demonstrating lifespan continuity, approximately 70% of participants, regardless of age, chose water and referenced current thirst as their rationale. Individual differences in working memory and undergraduate GPA were positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
54
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 56 publications
18
54
8
Order By: Relevance
“…As expected, no effect of age on pretzel task performance was found when 3‐ to 7‐year‐olds were asked to predict their own future preference. This finding is consistent with past studies that have also found no age‐related improvements in pretzel task performance between 3 years old and young adulthood (Atance & Meltzoff, ; Cheke & Clayton, ; Kramer et al, ; Mahy et al, ). Interestingly, many other episodic foresight tasks where present and future states do not conflict show age‐related improvements during the preschool years (e.g., Atance & Jackson, ; Suddendorf & Busby, ), suggesting that current‐future state conflict may pose special difficulty for making accurate future predictions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As expected, no effect of age on pretzel task performance was found when 3‐ to 7‐year‐olds were asked to predict their own future preference. This finding is consistent with past studies that have also found no age‐related improvements in pretzel task performance between 3 years old and young adulthood (Atance & Meltzoff, ; Cheke & Clayton, ; Kramer et al, ; Mahy et al, ). Interestingly, many other episodic foresight tasks where present and future states do not conflict show age‐related improvements during the preschool years (e.g., Atance & Jackson, ; Suddendorf & Busby, ), suggesting that current‐future state conflict may pose special difficulty for making accurate future predictions.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, low levels of performance on the pretzel task for self and other could, at least partially, be explained by children's general lack of understanding of physiological states. Yet children's at chance performance on the pretzel task for other compared with below chance performance for self suggest some support for the current‐state bias explanation (e.g., Kramer et al, ; Mahy, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, children's ability to both generate future mental scenarios and imbue these scenarios with rich contextual details has been shown to increase gradually between 5 and 11 years of age (Coughlin, Lyons, & Ghetti, 2014;Coughlin, Robins, & Ghetti, 2017), and there are continued age-related improvements in the richness of imagined events through to at least ages 14 to 16 years (Gott & Lah, 2014). Furthermore, recent studies (Atance & Meltzoff, 2006;Kramer, Goldfarb, Tashjian, & Lagattuta, 2017;Mahy, Grass, Wagner, & Kliegel, 2014) have revealed that affective and motivational aspects of episodic foresight, like the ability to accurately anticipate future desires and feelings, may be late developing. For example, Mahy et al found that 7-yearolds performed no better than 3-year-olds at predicting a future desire that differed from a current one.…”
Section: Developmentmentioning
confidence: 99%
“…In general, children as young as 4 years old have shown competence on tasks in which they are prompted to consider the future by being forced to select an item or through questioning (e.g., Atance & Meltzoff, 2005;Hayne, Gross, McNamee, Fitzgibbon, & Tustin, 2011;Payne, Taylor, Hayne, & Scarf, 2014;Suddendorf, Nielsen, & von Gehlen, 2011). However, recent studies show preschoolers perform rather poorly on tasks requiring them to self-generate future scenarios (Coughlin et al, 2014), spontaneously save for the future (Metcalf & Atance, 2011), and consider future desires that differ from current ones (Atance & Meltzoff, 2005;Kramer, Goldfarb, Tashjian, & Lagattuta, 2017;Mahy et al, 2014).…”
Section: Episodic Foresightmentioning
confidence: 99%